LIPID ANALYSIS IN HUMAN INTERVERTEBRAL DISC MATERIAL - OKTAY, G; GUNER, A; GUNER, G; KERMAN, M; PABUCCUOGLU, U (Portland Press Ltd, 1995)
[Abstract Not Available]
653rd Meeting of the Biochemical-Society-of-London -- SEP 13-16, 1994 -- UNIV SUSSEX, BRIGHTON, ENGLAND
Keywords: Serum; Cholesterol; Collagen